A novel fluorescent assay for uracil DNA glycosylase activity built on the 3′–5′ exonuclease activity-based endonuclease IV cyclic signal amplification strategy. (7th December 2020) - Tian, Jing-Xuan; Fang, Yan-Zhao; Yang, Yi-Xuan; Wu, Shuang; Xiao, Qiang; Kong, Xiang-Juan
Abstract : The unique 3′-5′ exonuclease activity of endonuclease IV to DNA strands has been demonstrated, which enables the development of a novel highly sensitive assay for UDG activity. Abstract : A unique 3′–5′ exonuclease activity of endonuclease IV (Endo IV) at the 3′ terminus of DNA has been demonstrated, which enabled the development of a novel 3′–5′ exonuclease activity-based Endo IV cyclic signal amplification strategy (EAECSA) for a highly sensitive uracil DNA glycosylase (UDG) activity assay. In this strategy, a hairpin probe with one uracil nucleotide is efficiently excised by UDG, yielding an apyrimidinic site (AP site). The AP site is cleaved by Endo IV and a shorter DNA probe is released to trigger the EAECSA strategy via the cyclic formation of a three-way junction, leading to the repeated digestion of the detection probe and the liberation of FAM-labeled single bases. Then, a strong fluorescence signal is observed due to the extremely weak interaction between the FAM-labeled single bases and GO. In contrast, when UDG is absent, the cleavage of the hairpin probe fails, the three-way junction structure is not formed, and no cleavage of the detection probe occurs, and thus, a negligible fluorescence signal is detected because the fluorophore of the detection probe is efficiently quenched by GO. The designed EAECSA technology demonstrated a detection limit of 7.0 × 10 −4 U mL −1 and showed a superb performance in screening UDG inhibitors, as well as cancer cell analysis. The proposed strategy provides a new way for isothermal nucleic acid amplification and may be promising for UDG profiling applications and related disease diagnosis.